Neuronal Cells Rearrangement During Aging and Neurodegenerative Disease: Metabolism, Oxidative Stress and Organelles Dynamic - Castelli, Vanessa; Benedetti, Elisabetta; Antonosante, Andrea; Catanesi, Mariano; Pitari, Giuseppina; Ippoliti, Rodolfo; Cimini, Annamaria; d’Angelo, Michele (Frontiers in Molecular Neuroscience, 2019)
Brain cells normally respond adaptively to oxidative stress or bioenergetic challenges, resulting from ongoing activity in neuronal circuits. During aging and in neurodegenerative disorders, these mechanisms are compromised. In fact, neurons show unique age-related changes in functions and metabolism, resulting in greater susceptibility to insults and disease. Aging affects the nervous system as well as other organs. More precisely, as the nervous system ages, neuron metabolism may change, inducing glucose hypometabolism, impaired transport of critical substrates underlying metabolism, alterations in calcium signaling, and mitochondrial dysfunction. Moreover, in neuronal aging, an accumulation of impaired and aggregated proteins in the cytoplasm and in mitochondria is observed, as the result of oxidative stress: reduced antioxidant defenses and/or increase of reactive oxygen species (ROS). These changes lead to greater vulnerability of neurons in various regions of the brain and increased susceptibility to several diseases. Specifically, the first part of the review article will focus on the major neuronal cells’ rearrangements during aging in response to changes in metabolism and oxidative stress, while the second part will cover the neurodegenerative disease areas in detail.